Combination of Wild ginger, Honey, and Probiotics as Growth Prometer Candidates : An in Vitro Study - Marlin Cindy Claudya Malelak; Agnesia Endang Tri Hastuti Wahyuni; Agustina Dwi Wijayanti; Vinsa Cantya Prakasita (Jurnal Sain Veteriner, 2022)
Growth Promoter Antibiotics are used to prevent disease and promote growth and production in poultry. Repeated admnistration of feed can have a microorganic resistance effect, accumulation of antibiotic residues in animal and environmental products and imbalance of normal microflora in the intestine. The antibacterial and carbohydrate content of some natural ingredients can be potential as a replacement candidate for AGP. This study aims to determine the role of a combination of wild ginger, honey, and probiotics (Bacillus subtilis and Lactobacillus acidophilus) as AGP candiate in Vitro. The antibacterial activity of the combination of wild ginger and honey against pathogens (E. coli) and their use against probiotics was tested by disk diffusion method, while the calculation of optical density values to determine the minimum inhibitory concentration and minimum bactericidal concentration was carried out on E. coli. The ability of inhibition of probiotics against pathogens is also done by the disk diffusion method. The disk diffusion test results showed the best combination was extract of 25% wild ginger aquades + 100% Lombok honey with inhibition zone diameter (8,53 ±, 03). Optical density values indicate this combination is able to inhibit and kill E. coli (DO 0,00 ±, 002) and support B. subtilis (DO 0,18 ±, 002) and L. acidophilus (DO 0.25 ±, 005) significantly better than positive control. MIC value of wild ginger aquades extract and honey combination against E. coli is wild ginger aquades extract 3.13% + Lombok honey 25%, while MBC value is wild ginger aquades extract 6,25% + Lombok honey 25%. The combination of B. subtilis and L. acidophilus showed the largest inhibitory zone diameter against E. coli (7,30 ±, 02 mm) compared to individual colonies. The combination of wild ginger and honey, in addition to inhibiting also able to kill pathogens and support the growth of probiotics, so this formula can be used as one of the replacement candidates for AGP.